Pengaruh Paket Cinta ASI terhadap Kecukupan ASI di Desa Pasir Tangkil Wilayah Kerja Puskesmas Baros - Izzati, Hefni Nurul; S, Sulastri (Universitas Malahayati, 2025)
ABSTRACT Breastfeeding Adequacy is one of the most effective ways to improve the health and survival of infants. One of the techniques to improve the quality of breast milk is the intervention of the love breast milk package. The purpose of this study was to determine the effect of the love breast milk package on the adequacy of breastfeeding at the Baros Public Health Center. This study uses a quantitative research design, with a Quasy Experimental with pre and post test without control with a sample of 20 mothers who are breastfeeding mothers aged 0-12 months without mixed formula milk. The results showed that the average respondent before the breastfeeding love package intervention was 35.85 with a standard deviation of 2.560 with a 95% CI 34.63-37.05 and the average respondent after the breastfeeding love package intervention was 40.35 with a standard deviation of 2.834. with 95% CI 39.02-41.68 . The increase in the mean value between before and after receiving the love breastfeeding package intervention was 4.50 with a standard deviation of 1.100. The results of the statistical test obtained a p value 0.000, it can be concluded that there is an effect of breastfeeding love packages on the adequacy of breastfeeding in Pasir Tangkil Village, Baros Health Center Work Area in 2024. There is an effect of breastfeeding love packages on the adequacy of breastfeeding Keywords: Love Breastfeeding Packages, Adequace Of Breast Milk ABSTRAK Kecukupan ASI merupakan salah satu cara yang efektif dalam meningkatkan kesehatan dan kelangusangan hidup bagi bayi. Salah satu tehnik untuk meningkatkan kualitas ASI yaitu dengan intervensi paket cinta ASI. Tujuan penelitian ini adalah mengetahui pengaruh paket cinta asi terhadap kecukupan ASI di puskesmas Baros. Mengetahui pengaruh paket cinta asi terhadap kecukupan ASI di puskesmas Baros Tahun 2024. Penelitian ini mengunakan desain penelitian kuantitatif, dengan rancangan penelitian Quasy Eksperimental dengan Pre and post test without control dengan sampel penelitian sebanyak 20 responden ibu yang sedang menyusui ASI usia 0-12 bulan tanpa di campur susu formula. Penelitian menunjukkan bahwa rata - rata responden sebelum intervensi paket cinta ASI adalah 35,85 dengan standar deviasi 2,560 dengan CI 95% 34,63-37,05 dan rata - rata responden sesudah intervensi paket cinta ASI adalah 40,35 dengan standar deviasi 2,834 dengan CI 95% 39,02-41,68 . Peningkatan nilai mean antara sebelum dan sesudah mendapat intervensi paket cinta ASI sebesar 4,50 dengan sandar deviasi 1,100. Hasil uji statistik didapat nilai p value 0,000, maka dapat disimpulkan terdapat pengaruh peket cinta ASI terhadap kecukupan ASI di Desa Pasir Tangkil Wilayah Kerja Puskesmas Baros Tahun 2024. Peket cinta ASI berpengaruh terhadap kecukupan ASI ibu menyusui. Penggunaan paket cinta dapat menngkatkan efektivitas kecukupan ASI ibu menyusui. Kata Kunci: Paket Cita ASI, Kecukupan ASI